Social Capital, Tourism and Socio-Economic Transformation of Rural Society: Evidence from Nepal - Martina Shakya (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
Tourism has a wide range of impacts on the economy, the natural environment and the people living in a destination. In the context of poor, rural societies, many scholars have emphasized the positive impacts of tourism on local economic growth. Concern has been voiced, however, about the social and cultural impacts of tourism due to observed changes in local norms, values and behaviour. This paper proposes the concept of social capital to analyze the social and cultural effects of tourism in Nepal. Empirical evidence from a household survey and four village case studies reveals a decline of bonding social capital and an increase in bridging social capital in the concerned communities. Tourism can exacerbate local conflicts and reduce the relevance of indigenous self-help mechanisms. At the same time, tourism has promoted the formation of new institutions and offers opportunities to develop and expand hierarchical, extra-community networks, which are an important precondition for upward economic mobility. Highlighting the interdependencies and trade-offs between economic advancement and changes in social capital, the paper calls for a more pragmatic and less normative academic debate on the social and cultural impacts of tourism in developing countries.
Keywords: 330; Social capital; Tourism; Poverty; Risk; Rural development; Nepal; Tourismus; Ländliche Entwicklung; Sozialkapital; Sozialer Wandel; Soziale Werte; Nepal; Entwicklungsländer